2023
DOI: 10.1038/s41598-023-43345-x
|View full text |Cite|
|
Sign up to set email alerts
|

Bacterial networks in Atlantic salmon with Piscirickettsiosis

Yoandy Coca,
Marcos Godoy,
Juan Pablo Pontigo
et al.

Abstract: An unbalanced composition of gut microbiota in fish is hypothesized to play a role in promoting bacterial infections, but the synergistic or antagonistic interactions between bacterial groups in relation to fish health are not well understood. We report that pathogenic species in the Piscirickettsia, Aeromonas, Renibacterium and Tenacibaculum genera were all detected in the digesta and gut mucosa of healthy Atlantic salmon without clinical signs of disease. Although Piscirickettsia salmonis (and other pathogen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 64 publications
0
2
0
Order By: Relevance
“…Therefore, [Cu(NN 1 ) 2 ]ClO 4 administration could potentially help shift the microbiota composition towards that observed in salmonids ( Kim et al, 2021 ). An increase in Pseudomonas was identified in O. mykiss , which has been recognized as potential probiotics in fish ( Vidal et al, 2023 ), with higher abundance in specimens surviving infectious processes ( Valdés et al, 2020 ; Coca et al, 2023 ). On the other hand, the reduction in the production of butyric acid-producing bacteria (Clostridiales), acting as an immunomodulator, could partly explain the effect on stimulating the immune response towards an inflammatory state ( Vargas et al, 2023 ).…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, [Cu(NN 1 ) 2 ]ClO 4 administration could potentially help shift the microbiota composition towards that observed in salmonids ( Kim et al, 2021 ). An increase in Pseudomonas was identified in O. mykiss , which has been recognized as potential probiotics in fish ( Vidal et al, 2023 ), with higher abundance in specimens surviving infectious processes ( Valdés et al, 2020 ; Coca et al, 2023 ). On the other hand, the reduction in the production of butyric acid-producing bacteria (Clostridiales), acting as an immunomodulator, could partly explain the effect on stimulating the immune response towards an inflammatory state ( Vargas et al, 2023 ).…”
Section: Discussionmentioning
confidence: 99%
“…Finally, it was observed that the administration of the compound surprisingly increased the abundance of bacteria of the genus Piscirickettsia, to which P. salmonis belongs. However, it has been reported that this bacterium is part of the intestinal microbiota of healthy fish, and that an imbalance in the composition of the microbiota and the interaction between different metabolites of various bacteria generates the appearance of SRS [67]. These data are relevant when interpreting our results, because although the compound generated an increase in this bacterial genus, the administration of [Cu(NN 1 ) 2 ]ClO 4 during the challenge with P. salmonis generated protection, considerably increasing the survival of Atlantic salmon.…”
Section: Discussionmentioning
confidence: 99%